2011
DOI: 10.1016/j.mechmachtheory.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Half-turns and line symmetric motions

Abstract: A line symmetric motion is the motion obtained by reflecting a rigid body in the successive generator lines of a ruled surface. In this work we review the dual quaternion approach to rigid body displacements, in particular the representation of the group SE(3) by the Study quadric. Then some classical work on reflections in lines or half-turns is reviewed. Next two new characterisations of line symmetric motions are presented. These are used to study a number of examples one of which is a novel line symmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 14 publications
(17 reference statements)
0
26
0
Order By: Relevance
“…The For solution E it was already shown by the author in [18] that the self-motion is a line-symmetric motion. This follows directly from the property e 0 = f 0 = 0 under consideration of the result given by Selig and Husty [23].…”
Section: Discussing Solutions A-fmentioning
confidence: 73%
“…The For solution E it was already shown by the author in [18] that the self-motion is a line-symmetric motion. This follows directly from the property e 0 = f 0 = 0 under consideration of the result given by Selig and Husty [23].…”
Section: Discussing Solutions A-fmentioning
confidence: 73%
“…In [4] it was shown that this equation characterises line-symmetric motions, moreover, line-symmetric motions were shown to lie in the intersection of the Study quadric with a 5-plane.…”
Section: Line-symmetry and Translationsmentioning
confidence: 99%
“…According to [25], this is one possible characterization of line-symmetric motions. In general, the curve s is a regular conic section, but it can also happen that it consists of one or two straight lines, implying Schönflies self-motions.…”
Section: Generalized Dietmaier Self-motionsmentioning
confidence: 99%
“…These planar hexapods with so-called Type 2 DM (=Darboux-Mannheim) self-motions do not possess the global symmetry property any longer, but their self-motions are still line-symmetric ones (cf. [25]). In this context, it should finally be noted that most of the known hexapodal self-motions (cf.…”
Section: Hexapodal Self-motions Viewed Under the Aspect Of Symmetrymentioning
confidence: 99%